Eco-Friendly Pest Balls from Waste Cooking Oil and Herbal Plant Residues as a Substitute for Naphthalene (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Naphthalene, a polycyclic aromatic hydrocarbon used extensively in mothballs, poses well-documented risks to human health and the environment due to its toxicity, persistence, and capacity for bioaccumulation. Concurrently, increasing volumes of household waste, particularly used cooking oil and discarded herbal plant residues which contribute to escalating environmental burdens. This study integrates waste valorisation and green chemistry principles to develop biodegradable pest-repellent balls as an eco-friendly alternative to naphthalene products. Waste cooking oil underwent pretreatment, and herbal residues were processed into fine powders for incorporation into pest ball formulations. The optimal base composition was determined to be a mixing with glycerin-to-sodium hydroxide ratio of 2:1. One-way ANOVA revealed significant differences (p < 0.05) in percentage repellency (%RI), with performance ranked as cinnamon > clove > lemongrass > lemon > orange. Monthly longevity followed the order orange > clove > lemon > lemongrass > cinnamon, suggesting greater biodegradability for cinnamon-based formulations. Although the initial cost of the alternative pest ball may be slightly higher than the of commercial mothballs, the potential of converting household waste into effective, biodegradable pest control solutions makes it a more cost-effective and sustainable solution, offering greater value for health, safety, and the environment. These findings simultaneously address toxic chemical exposure and waste management challenges.
Keywords: Naphthalene; Waste cooking oil; Herbal plant residue; Cinnamon; Eco-friendly alternative